Compressed Natural Gas (CNG) Policy Acceptance among Urban-Private-Passenger-Commercial-Transporters in South-West, Nigeria - Rotimi Adeforiti (Journal of Governance, 2026)
Nigeria has had a history of sustained increases in the price of fossil fuel spanning over four decades probably conditioning users including Urban-Private-Passenger-Commercial-Transporter, UPPCT, on the replication of the same on CNG, and their conditioning acceptance as automotive fuel. The study identified factors sustaining fossil fuel use and analysed factors affecting the adoption and use of CNG by UPPCT in South-West, Nigeria. The study is based on the assumption that the expected increase in the price of CNG is influencing its use. The Innovation Diffusion Theory propounded by Rogers, the Political Systems Theory of David Easton, and the Theory of Planned Behaviour as expatiated by Ajzen (1991) were harmonised and applied to the study that while innovation emerges, it is fed into the political system as a demand or support in the form of input, and produced as a government policy. An individual accepts government policy based on previous experience and projected outcomes. The study adopted an exploratory research design, both the Systematic Literature Review and the Catch-Sampling Intercept Surveys served as a source of information for the study. Internal and external factors are responsible for the continuous use of fossil fuels among the UPPCT. Also, the adoption of CNG by UPPCT is conditioned by the cost of conversion of a vehicle to CNG, inadequate CNG fuelling station, and the expected increase in price on adoption. The study concluded that the acceptance of CNG by UPPCT is conditioned by the environmental factors that exist as internal and external realities. The study encourages the government to intensify its orientation on CNG, provide adequate finance for expansion, and subside the conversion process to CNG.